Math, asked by Roastie, 3 months ago


By what number should
(- 2/3)^-1
be multiplied so that the product becomes
(-3/4)^-1?​

Answers

Answered by 4779
3

Answer:

8/9

Step-by-step explanation: Let's assume the missing number to be y.

We know that (-2/3)^-1 * y = (-3/4)^-1.

(-2/3)^-1 can be written as -3/2 and (-3/4)^-1 can be written as -4/3.

New equation : -3/2 * y = -4/3.

Then y = -4/3 / -3/2. (Dividing both sides by -3/2).

y = -4/3 * -2/3

y = 8/9.

Please mark it as the brainliest.

Similar questions